Standardised innovation management systems: A case study of the Spanish Standard UNE 166002:2006 - Moisés Mir; Martí Casadesús (Innovar: Revista de Ciencias Administrativas y Sociales, 2011)
This paper describes the experience of a Spanish manufacturing firm that implemented the UNE 166002:2006 standard, which is the first in the world to offer a certifiable standardised management system for innovation. After a brief review of innovation management in general, the paper describes the history, objectives, and content of the UNE 166002:2006 Spanish standard and the family of standards to which it belongs. The paper then presents a case study of the implementation of the standard in a manufacturing company, describing the benefits and difficulties of the implementation as detected by the company personnel involved. The paper concludes with a discussion of the desirability and feasibility of creating an international innovation management standard and a new generation of innovation management processes based on a standard for innovation